Isolamento e clonagem do gene que codifica a lipase do fungo endomelanconiopsis endophytica - Carvalho Neto, Francisco Geraldo Mello da Rocha (2013)
Scientific discoveries and technological advances in the field of molecular biology of proteins, especially in the late 19th and early 20th century, contributed to the employment of biocatalysts by industries. This way, enzymes started to occupy an important role in economically profitable activities. Lipases are among the hydrolytic enzymes of great interest, because they are versatile biocatalysts, capable to catalyze various reactions, both in aqueous and organic medium with water content restricted. Although lipase are widely distributed, it can be said that these enzymes are the most studied and exploited for its expression and production by fungi. In microorganisms, lipases are able to show phospholipid activity, being used as a defense mechanism, since when secreted, they provide competition with the microflora; facilitate the digestion of lipids and fatty acids released assist in tissue adhesion, cell-cell and cell-host. In this work, we isolated the lipase gene of the fungus Endomelanconiopsis endophytica through several molecular biology tools, such as the extraction of mRNA and synthesis of double stranded cDNA.